1997
DOI: 10.1152/ajpcell.1997.272.5.c1513
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characterization of an intestinal subepithelial myofibroblast cell line

Abstract: Subepithelial myofibroblasts are located at the interface between the epithelium and lamina propria in most mucosal tissues. Their biological functions are largely unknown because a long-term cell culture model for these cells has not been available. In this report, we define the phenotypic properties of a human colonic cell line (18Co) that exhibits most of the known characteristics of intestinal subepithelial myofibroblasts in situ. These characteristics include 1) a cell shape that can be reversibly interco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
79
0
7

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 29 publications
0
79
0
7
Order By: Relevance
“…The human colonic subepithelial myofibroblast cell line, 18Co was obtained from the American Type Culture Collection (CRL-1459) and maintained as described previously (56). Culture media, supplements, and subculturing reagents were purchased from Sigma.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The human colonic subepithelial myofibroblast cell line, 18Co was obtained from the American Type Culture Collection (CRL-1459) and maintained as described previously (56). Culture media, supplements, and subculturing reagents were purchased from Sigma.…”
Section: Methodsmentioning
confidence: 99%
“…As such, the COX-2 gene is subject to regulation by numerous signaling pathways, and the relative contribution of each depends upon the stimulus, the cellular environment, and the particular cell type. We have characterized a myofibroblast cell line, 18Co, derived from mucosal biopsy of human neonatal colon, which exhibits the phenotypic features of primary ISEMF cultures and ISEMFs in situ (56). Herein, using IL-1 as a model stimulus, we report the first detailed analysis of signaling pathways important for COX-2 expression in human intestinal myofibroblasts and how these pathways interact with each other.…”
mentioning
confidence: 99%
“…A commercially available human CMF primary isolate, 18Co, was also used as a representative CMF (45). Phenotypic characterization of cultured CMFs and 18Co cells has demonstrated that they are uniformly positive for ␣-SMA and CD90, but negative for desmin (Fig.…”
Section: Cmfs Express Mhc Class II Molecules In Vitromentioning
confidence: 99%
“…MYOFIBROBLASTS ARE LOCATED in the lamina propria of the intestine in close proximity to epithelial cells and have ultrastructural features of both smooth muscle cells and fibroblasts (38). They are paracrine cells that regulate a number of fundamental biological processes in the intestine, including epithelial chloride secretion (11), which, in turn, controls the secretion of water into the intestinal lumen.…”
mentioning
confidence: 99%